A magnetic γ-Fe2O3@PANI@TiO2 core–shell nanocomposite for arsenic removal via a coupled visible-light-induced photocatalytic oxidation–adsorption process. Issue 5 (9th April 2020) - Wang, Yuan; Zhang, Ping; Zhang, Tian C.; Xiang, Gang; Wang, Xinlong; Pehkonen, Simo; Yuan, Shaojun
Abstract : A magnetic γ-Fe2 O3 @PANI@TiO2 nanocomposite acts as an efficient photocatalyst coupled with adsorption for arsenic removal. It could achieve a good capacity of As(iii ) removal under visible light. Abstract : Arsenic polluted groundwater impairs human health and poses severe threats to drinking water supplies and ecosystems. Hence, an efficient method of simultaneous oxidation of As(iii ) to As(v ), and removal of As(v ) from water has triggered increasing attention. In this study, a magnetic γ-Fe2 O3 core–shell heterojunction nanocomposite was synthesized by means of hydrothermal crystallization of TiO2 on the surface of the magnetic core–shell loaded with polyaniline (γ-Fe2 O3 @PANI@TiO2 ). As an efficient photocatalyst coupled with adsorption, γ-Fe2 O3 @PANI@TiO2 has a high light utilization and good adsorption capacity. Notably, the nanocomposite has excellent stability at various initial pH values with good reusability. Among the co-existing ions investigated, PO4 3− has the greatest competitive reaction. The photocatalytic oxidation of As(iii ) on γ-Fe2 O3 @PANI@TiO2 is dominated by the synergy of several active substances, with superoxide free radicals and photogenerated holes being the major players.